Distribution of the Sunda Colugo (Galeopterus variegatus) in Malaysia (Peninsular, Sabah, Sarawak) - Muhammad Dzulhelmi Muhammad Nasir,; Mohd Tajuddin Abdullah, (Tropical Life Sciences Research, 2010)
There is not much information available on the distribution of the Sunda colugo (Galeopterus variegates) in Malaysia, despite it being one of only two known species in the order Dermoptera. Data on the presence of the Sunda colugo and the vernacular names used by various ethnic groups throughout Malaysia were collected and compiled from various primary and secondary sources. There were 27 locations from Peninsular, 11 locations from Sabah and 34 locations from Sarawak that reported the presence of the Sunda colugo throughout Malaysia. The various ethnic groups of Malaysia adopted 37 different vernacular names to describe the Sunda colugo. This baseline data can be useful for the management authorities in conducting periodic monitoring and will enhance our knowledge of the population dynamics of the Sunda colugo in Malaysia. Terdapat hanya sedikit maklumat mengenai Kubong [Sunda colugo] (Galeopterus variegates) di Malaysia walaupun kubong merupakan salah satu daripada dua spesis di dalam kumpulan Dermoptera. Maklumat kewujudan Kubong dan nama tempatan yang digunakan telah dikumpul dari pelbagai sumber utama dan sekunder. Terdapat 27 lokasi dari Semenanjung, 11 lokasi dari Sabah dan 34 lokasi dari Sarawak yang merekodkan kewujudan Kubong di seluruh Malaysia. Pelbagai kumpulan etnik dari seluruh Malaysia telah mengadaptasi sebanyak 37 nama tempatan untuk Kubong. Data ini adalah amat berguna kepada pihak pengurusan dalam menjalankan pemantauan berkala bagi meningkatkan ilmu pengetahuan mengenai kewujudan dan taburan Kubong di Malaysia.